Multimodal mass spectrometry - Raman imaging reveals solvent dependent structural and chemical tissue alterations - Gabor Toth; Adrianna Kryska; Anna Sroka-Bartnicka; Ingela Lanekoff (Analytica Chimica Acta, 2025)

Chronic impairment of neurovascular coupling and cognitive decline in young survivors of severe traumatic brain injury - Zsofia Dina Magyar-Sumegi; Mark Csendes; Dominika Lendvai-Emmert; Gabriella Sebestyen; Viktoria Tamas; Szabolcs Bandi; Andras Czigler; Andriy Yabluchanskiy; Stefano Tarantini; Zoltan Ungvari; Endre Czeiter; Krisztina Amrein; et al. (GeroScience, 2025)
Severe traumatic brain injury (TBI) leads to chronic cognitive decline, imposing a significant societal burden. The regulation of cerebral blood flow (CBF) is critical for cognitive function, and acute disruptions in CBF regulation predict poor TBI outcomes. However, the long-term effects of TBI on CBF regulation and their association with cognitive function remain poorly understood. This study aimed to investigate whether severe TBI results in chronic CBF dysregulation and whether this contributes to long-term cognitive deficits. Additionally, we examined the role of TBI-induced insulin-like growth factor 1 (IGF-1) deficiency in cerebrovascular dysfunction. We assessed cognitive function, basal CBF (via phase contrast MRI), CBF autoregulation (via transcranial Doppler), and neurovascular coupling (NVC) in 33 TBI survivors (mean age 37.6 years, ~ 10 years post-injury) and 21 age-matched healthy controls. Serum IGF-1 levels were also measured. TBI survivors exhibited significant impairments in memory and executive function compared to controls. While basal CBF and autoregulation remained intact, NVC responses were chronically impaired and correlated with cognitive deficits. However, IGF-1 levels did not differ between groups and were not associated with NVC impairment or cognitive function. Our findings indicate that severe TBI results in chronic impairment of neurovascular coupling, which likely contributes to long-term cognitive deficits. These results highlight the need for further research to identify underlying neurovascular mechanisms and develop interventions to restore NVC and cognitive function in TBI survivors.

Age-related decline in circulating IGF-1 associates with impaired neurovascular coupling responses in older adults - Luca Toth; Andras Czigler; Emoke Hegedus; Hedvig Komaromy; Krisztina Amrein; Endre Czeiter; Andriy Yabluchanskiy; Akos Koller; Gergely Orsi; Gabor Perlaki; Attila Schwarcz; Andras Buki; et al. (GeroScience, 2022)
Impairment of moment-to-moment adjustment of cerebral blood flow (CBF) to the increased oxygen and energy requirements of active brain regions via neurovascular coupling (NVC) contributes to the genesis of age-related cognitive impairment. Aging is associated with marked deficiency in the vasoprotective hormone insulin-like growth factor-1 (IGF-1). Preclinical studies on animal models of aging suggest that circulating IGF-1 deficiency is causally linked to impairment of NVC responses. The present study was designed to test the hypotheses that decreases in circulating IGF-1 levels in older adults also predict the magnitude of age-related decline of NVC responses. In a single-center cross-sectional study, we enrolled healthy young ( n = 31, 11 female, 20 male, mean age: 28.4 + / − 4.2 years) and aged volunteers ( n = 32, 18 female, 14 male, mean age: 67.9 + / − 4.1 years). Serum IGF-1 level, basal CBF (phase contrast magnetic resonance imaging (MRI)), and NVC responses during the trail making task (with transcranial Doppler sonography) were assessed. We found that circulating IGF-1 levels were significantly decreased with age and associated with decreased basal CBF. Age-related decline in IGF-1 levels predicted the magnitude of age-related decline in NVC responses. In conclusion, our study provides additional evidence in support of the concept that age-related circulating IGF-1 deficiency contributes to neurovascular aging, impairing CBF and functional hyperemia in older adults.

Effects of pituitary adenylate cyclase activating polypeptide (PACAP) in corneal epithelial regeneration and signal transduction in rats - Peter Kiss; Jozsef Farkas; Krisztina Kovacs; Valeria Gaal; Zsolt Biro; Aliz Szabo; Tamas Atlasz; Inez Bosnyak; Gabor Toth; Andrea Tamas; Dora Reglodi (International Journal of Peptide Research and Therapeutics, 2022)
Corneal epithelium responds to insults with a rapid wound healing, which is essential for maintaining vision. The proper balance of apoptotic and proliferation-stimulating pathways is critical for normal regeneration. Pituitary adenylate cyclase activating polypeptide (PACAP) is an important growth factor during the development of the nervous system and exerts cytoprotective effects in injuries. The aim of the present study was to investigate the effects of PACAP on corneal epithelial wound healing in rats and on two important protective signaling molecules, Akt and ERK1/2, both of which have been reported to play important roles during cell survival and regeneration, including corneal wound healing. Wistar rats received PACAP treatment in form of eyedrops, containing 1, 5 and 10 µg PACAP27, immediately and every two hours after corneal abrasion. Corneas were stained with fluorescein dye and further processed for histological staining or Western blot analysis for Akt and ERK1/2 expression. Our results showed that topical PACAP application enhanced corneal wound healing, as the area of injury was significantly less in PACAP-treated groups. Furthermore, both ERK1/2 and Akt signaling was induced upon PACAP administration in both injured and intact corneas. In summary, the present results show that PACAP enhances corneal wound healing in a rat model of corneal abrasion.

Cerebral venous congestion exacerbates cerebral microhemorrhages in mice - Adam Nyul-Toth; Gabor A. Fulop; Stefano Tarantini; Tamas Kiss; Chetan Ahire; Janet A. Faakye; Anna Ungvari; Peter Toth; Attila Toth; Anna Csiszar; Zoltan Ungvari (GeroScience, 2022)

Stability Test of PACAP in Eye Drops - Anita K. Kovacs; Tamas Atlasz; Dora Werling; Edina Szabo; Dora Reglodi; Gabor K. Toth (Journal of Molecular Neuroscience, 2021)
PACAP is a neuropeptide with widespread distribution and diverse biological functions. It has strong cytoprotective effects mediated mainly through specific PAC1 receptors. Experimental data show protective effects of PACAP in the retina and cornea in several pathological conditions. Although intravitreal injections are a common practice in some ocular diseases, delivery of therapeutic agents in the form of eye drops would be more convenient and would lead to fewer side effects. We have previously shown that PACAP, in the form of eye drops, is able to pass through the ocular barriers and can exert retinoprotective effects. As eye drops represent a promising form of administration of PACAP in ocular diseases, it is important to investigate the stability of PACAP in solutions used in eye drops. In this study, the stability of PACAP1-27 and PACAP1-38 in eye drops was measured in four common media and a commercially available artificial tear solution at both room temperature and +4 °C. Mass spectrometry results show that the highest stability was gained with PACAP1-38 in water and 0.9% saline solution at +4 °C, representing 80–90% drug persistence after 2 weeks. PACAP1-38 in the artificial tear showed very fast degradation at room temperature, but was stable at +4 °C. In summary, PACAP1-38 has higher stability than PACAP1-27, with highest stability at +4 °C in water solution, but both peptides in each medium can be stored for relatively longer periods without significant degradation. These data can provide reference for future therapeutic use of PACAP in eye drops.

Cerebral venous congestion promotes blood-brain barrier disruption and neuroinflammation, impairing cognitive function in mice - Gabor A. Fulop; Chetan Ahire; Tamas Csipo; Stefano Tarantini; Tamas Kiss; Priya Balasubramanian; Andriy Yabluchanskiy; Eszter Farkas; Attila Toth; Ádám Nyúl-Tóth; Peter Toth; Anna Csiszar; et al. (GeroScience, 2019)

Demonstration of impaired neurovascular coupling responses in TG2576 mouse model of Alzheimer’s disease using functional laser speckle contrast imaging - Stefano Tarantini; Gabor A. Fulop; Tamas Kiss; Eszter Farkas; Dániel Zölei-Szénási; Veronica Galvan; Peter Toth; Anna Csiszar; Zoltan Ungvari; Andriy Yabluchanskiy (GeroScience, 2017)

PACAP Is Protective in a Rat Model of Retinopathy of Prematurity - Timea Kvarik; Barbara Mammel; Dora Reglodi; Krisztina Kovacs; Dora Werling; Brigitta Bede; Alexandra Vaczy; Eszter Fabian; Gabor Toth; Peter Kiss; Andrea Tamas; Tibor Ertl; et al. (Journal of Molecular Neuroscience, 2016)

Characterization of the Thermoregulatory Response to Pituitary Adenylate Cyclase-Activating Polypeptide in Rodents - Eszter Banki; Eszter Pakai; Balazs Gaszner; Csaba Zsiboras; Andras Czett; Paras Rahul Parkash Bhuddi; Hitoshi Hashimoto; Gabor Toth; Andrea Tamas; Dora Reglodi; Andras Garami (Journal of Molecular Neuroscience, 2014)

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Induces Relaxations of Peripheral and Cerebral Arteries, which are Differentially Impaired by Aging - Zoltan Vamos; Ivan Ivic; Peter Cseplo; Gabor Toth; Andrea Tamas; Dora Reglodi; Akos Koller (Journal of Molecular Neuroscience, 2014)

PACAP Application Improves Functional Outcome of Chronic Retinal Ischemic Injury in Rats-Evidence From Electroretinographic Measurements - Bese Danyadi; Krisztina Szabadfi; Dora Reglodi; Agoston Mihalik; Tibor Danyadi; Zsolt Kovacs; Istvan Batai; Andrea Tamas; Peter Kiss; Gabor Toth; Robert Gabriel (Journal of Molecular Neuroscience, 2014)

Molecular Mechanisms Underlying the Nephroprotective Effects of PACAP in Diabetes - Eszter Banki; Krisztina Kovacs; Daniel Nagy; Tamas Juhasz; Peter Degrell; Katalin Csanaky; Peter Kiss; Gabor Jancso; Gabor Toth; Andrea Tamas; Dora Reglodi (Journal of Molecular Neuroscience, 2014)

Influence of Terminal Differentiation and PACAP on the Cytokine, Chemokine, and Growth Factor Secretion of Mammary Epithelial Cells - Katalin Csanaky; Wolfgang Doppler; Andrea Tamas; Krisztina Kovacs; Gabor Toth; Dora Reglodi (Journal of Molecular Neuroscience, 2014)

Effects of PACAP in UV-A Radiation-Induced Retinal Degeneration Models in Rats - Tamas Atlasz; Krisztina Szabadfi; Peter Kiss; Zsuzsanna Marton; Monika Griecs; Levente Hamza; Valeria Gaal; Zsolt Biro; Andrea Tamas; Gabor Hild; Miklos Nyitrai; Gabor Toth; et al. (Journal of Molecular Neuroscience, 2011)

Protective Effect of PACAP Against Doxorubicin-Induced Cell Death in Cardiomyocyte Culture - Boglarka Racz; Dora Reglodi; Gabriella Horvath; Andras Szigeti; Borbala Balatonyi; Erzsebet Roth; Gyorgy Weber; Nasri Alotti; Gabor Toth; Balazs Gasz (Journal of Molecular Neuroscience, 2010)

Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) and Its Receptors Are Present and Biochemically Active in the Central Nervous System of the Pond Snail Lymnaea stagnalis - Zsolt Pirger; Zita Laszlo; Laszlo Hiripi; Laszlo Hernadi; Gabor Toth; Andrea Lubics; Dora Reglodi; Gyorgy Kemenes; Laszlo Mark (Journal of Molecular Neuroscience, 2010)

Effects of PACAP on Mitochondrial Apoptotic Pathways and Cytokine Expression in Rats Subjected to Renal Ischemia/Reperfusion - Gabriella Horvath; Boglarka Racz; Dora Reglodi; Krisztina Kovacs; Peter Kiss; Ferenc Gallyas; Zita Bognar; Aliz Szabo; Tamas Magyarlaki; Eszter Laszlo; Andrea Lubics; Andrea Tamas; et al. (Journal of Molecular Neuroscience, 2010)

Effects of PACAP on the Circadian Changes of Signaling Pathways in Chicken Pinealocytes - Boglarka Racz; Gabriella Horvath; Nandor Faluhelyi; Andras D. Nagy; Andrea Tamas; Peter Kiss; Ferenc Gallyas; Gabor Toth; Balazs Gaszner; Valer Csernus; Dora Reglodi (Journal of Molecular Neuroscience, 2008)

Effects of PACAP on Survival and Renal Morphology in Rats Subjected to Renal Ischemia/Reperfusion - Peter Szakaly; Peter Kiss; Andrea Lubics; Tamas Magyarlaki; Andrea Tamas; Boglarka Racz; Istvan Lengvari; Gabor Toth; Dora Reglodi (Journal of Molecular Neuroscience, 2008)

PACAP Has Anti-apoptotic Effect in the Salivary Gland of an Invertebrate Species, Helix pomatia - Zsolt Pirger; Jozsef Nemeth; Laszlo Hiripi; Gabor Toth; Peter Kiss; Andrea Lubics; Andrea Tamas; Laszlo Hernadi; Tibor Kiss; Dora Reglodi (Journal of Molecular Neuroscience, 2008)

Investigation of the Effects of PACAP on the Composition of Tear and Endolymph Proteins - Valeria Gaal; Laszlo Mark; Peter Kiss; Ildiko Kustos; Andrea Tamas; Bela Kocsis; Andrea Lubics; Viktoria Nemeth; Adrienn Nemeth; Laszlo Lujber; Jozsef Pytel; Gabor Toth; et al. (Journal of Molecular Neuroscience, 2008)

Survival motor Neuron protein regulates apoptosis in anin vitro model of Spinal muscular atrophy - Graham C. Parker; Xingli Li; Roumen A. Anguelov; Gabor Toth; Adam Cristescu; Gyula Acsadi (Neurotoxicity Research, 2008)

Postural control in athletes participating in an ironman triathlon - Edit Nagy; Kalman Toth; Gabor Janositz; Gyula Kovacs; Anna Feher-Kiss; Lajos Angyan; Gyngyi Horvath (European Journal of Applied Physiology, 2004)